Austenitic stainless steel
An austenitic stainless steel with controlled Cr, Mo, Ag, and N composition addresses microcorrosion issues and metal ion elution, offering enhanced resistance and cost-effective production.
Patent Information
- Application Number
- JP2022052400
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-03-28
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-03-28
AI Technical Summary
Austenitic stainless steels used in medical implants lack sufficient microcorrosion resistance in the passive region, leading to metal ion elution, and their production involves high costs due to electroslag remelting (ESR).
Austenitic stainless steel composition with controlled amounts of Cr, Mo, Ag, and N, satisfying the formula [Cr]+3.3[Mo]≧25.0, enhances microcorrosion resistance by suppressing micro-pit formation and metal ion elution, avoiding ESR.
The steel exhibits superior microcorrosion resistance in the passive region, reducing metal ion elution and manufacturing costs through optimized composition and production methods.
Smart Images

Figure 0007609109000002 
Figure 0007609109000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an austenitic stainless steel having excellent micro-corrosion resistance in the passive region. [Background technology]
[0002] In recent years, titanium alloys, cobalt-chromium alloys, and stainless steels are widely used as materials for medical devices, including implants. Stainless steel for medical devices must be austenitic, which is a non-magnetic structure, in order to prevent accidents during MRI (magnetic resonance imaging) examinations.
[0003] Furthermore, in order to accommodate patients with metal allergies, stainless steels for medical equipment are intended to have a composition in which the Ni content is kept as low as possible (for example, to 12.0 mass% or less). For this reason, high-N austenitic stainless steels have been developed that ensure the stability of the austenitic structure and the passive film by increasing the N content as a replacement for Ni.
[0004] An example of such a high-N austenitic stainless steel is stainless steel specified in ISO 5832-9, which has a composition containing, by mass%, 19.5-22.0% Cr, 9.0-11.0% Ni, 2.0-3.0% Mo, 2.0-4.25% Mn, and 0.25-0.50% N. This stainless steel is used as a material for artificial hip joint implants.
[0005] In addition, Patent Document 1 states: "A high-strength, highly corrosion-resistant nonmagnetic stainless steel containing, by mass percent (same below), C: 0.15% or less, Si: 1.0% or less, Mn: 3.0 to 12.0%, P: 0.030% or less, Ni: 0.50% or less, Cr: 15.0 to 21.0%, N: 0.70 to 1.50%, Al: 0.020% or less, and O: 0.020% or less, with the balance being Fe and unavoidable impurities." has been disclosed. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 4538966 Summary of the Invention [Problem to be solved by the invention]
[0007] From the viewpoint of biocompatibility, austenitic stainless steels used in living bodies are required to prevent the metal elements in the steel from ionizing and dissolving (hereinafter, also referred to as preventing the dissolution of metal ions). As has become clear from the studies of the inventors described below, to prevent the dissolution of metal ions, it is not enough to have excellent pitting corrosion resistance (resistance to pores) but it is also necessary to have excellent micro-corrosion resistance in the passive region.
[0008] In this regard, the stainless steel specified by ISO 5832-9 and the austenitic stainless steel disclosed in Patent Document 1 do not take into consideration the inhibition of microcorrosion, and microcorrosion resistance in the passive region is not guaranteed. Also, in order to include 0.70 mass% or more of N in steel, as in the austenitic stainless steel disclosed in Patent Document 1, electroslag remelting (ESR) must be used, which also poses the problem of a significant increase in manufacturing costs.
[0009] The present invention has been developed in view of the above-mentioned circumstances, and has an object to provide an austenitic stainless steel having excellent micro-corrosion resistance in the passive region.
[0010] Here, "excellent micro-corrosion resistance in the passive region" refers to a state where austenitic stainless steel test pieces are immersed in a test solution, and the current density is increased from the natural immersion potential to a current density of 1.1 mA cm in accordance with the method for measuring pitting corrosion potential specified in JIS G 0577. -2This means that when the potential is swept in the noble direction up to a potential reaching 0.01V, the current frequency in the potential range of 200 to 400 mV vs. Ag / AgCl is less than 250. The test solution used was a 0.9 mass% NaCl aqueous solution at 37°C without degassing, and the potential sweep rate was 20 mV min -1 The current frequency was measured continuously every 1 s in the potential range of 200 to 400 mV vs. Ag / AgCl, and the current density was measured at a frequency of 1 μA cm -2 If no micropits are formed due to partial destruction of the passive film, the current density in the potential range of 200 to 400 mV vs. Ag / AgCl is usually 1 μA cm -2 Since the current oscillation frequency is less than 100 Hz, the current oscillation frequency is counted as described above. [Means for solving the problem]
[0011] The inventors have conducted extensive research in order to solve the above problems. First, the inventors produced various steels simulating the composition specified in ISO 5832-9, specifically, steels having a composition containing, by mass%, 19.5-22.0% Cr, 9.0-11.0% Ni, 2.0-3.0% Mo, and 0.20% or more N, and measured the pitting potential of each steel in a 0.9 mass% NaCl aqueous solution at 37°C, simulating the condition inside a living body.
[0012] As a result, the pitting potential was 900mV vs. Ag / AgCl or higher for all steels, and there was no problem with pitting corrosion resistance. However, the elution of metal ions was confirmed for all steels.
[0013] Therefore, the inventors believed that excellent pitting corrosion resistance alone was insufficient to prevent the elution of metal ions, and further investigated the cause of the elution of metal ions. the result, In the above steels where the elution of metal ions was confirmed, many minute current oscillations were generated in the passive region, and The above-mentioned minute current vibrations are caused by the formation and repair of micro-pits on the steel surface. I found out.
[0014] That is, when minute current oscillations occur in the passive region, even if the passive film is maintained macroscopically, the passive film is partially destroyed and micropits are formed microscopically, and metal elements are ionized and eluted from the micropits during the time from when the micropits are formed until they are repaired (the passive film is formed again in the destroyed area). Here, the phenomenon in which metal elements are ionized and eluted from the micropits is called microcorrosion, and the ability to inhibit this microcorrosion is called microcorrosion resistance.
[0015] The passive region is one of the potential ranges on the anodic polarization curve obtained by immersing an austenitic stainless steel in a test solution that simulates the inside of a living body (hereinafter referred to as a biological solution), and then polarizing the austenitic stainless steel in the noble direction (anodic direction) from the natural immersion potential. For example, the passive region is the region where the current density is stably 1 μA cm as shown in Figure 1. -2 The potential range maintained is 200-400mV vs. Ag / AgCl.
[0016] Based on the above findings, the inventors have conducted further studies to suppress the generation of micropits in the passive region and inhibit the elution of metal ions, in other words, to improve the microcorrosion resistance in the passive region. As a result, the inventors discovered that by incorporating an appropriate amount of Ag together with an appropriate amount of N in the composition of austenitic stainless steel, the above-mentioned minute current oscillations can be suppressed, and the elution of harmful metal elements can be prevented. The inventors believe that the reason for this is that Ag in the steel binds with chloride ions in the simulated biological fluid, weakening the attack of the chloride ions on the passive film, and as a result, passivation by dissolved N is promoted (hereinafter, also referred to as the passivation effect by dissolved N). Ag is considered to be non-toxic to living organisms.
[0017] Based on the above findings, the inventors have further studied and found that the composition of the austenitic stainless steel is appropriately controlled, particularly in terms of mass%, Cr: 18.0% or more and 25.0% or less, Mo: 1.50% or more and 3.50% or less, Ag: 0.04% to 0.20% and N: 0.20% or more and 0.35% or less It has been discovered that by incorporating N and satisfying the relationship in the following formula (1), the passivation effect of the dissolved N is maximized, resulting in significantly superior microcorrosion resistance compared to conventional methods. [Cr]+3.3[Mo]≧25.0 (1) The present invention was completed based on the above findings and through further investigation.
[0018] That is, the gist and configuration of the present invention are as follows. 1. In mass percent, C: 0.100% or less, Si: 2.00% or less, Mn: 2.00% or more and 7.00% or less, P: 0.070% or less, S: 0.030% or less, Cr: 18.0% or more and 25.0% or less, Mo: 1.50% or more and 3.50% or less, Ni: 5.0% or more and 12.0% or less, Ag: 0.04% to 0.20% and N: 0.20% or more and 0.35% or less and the balance being Fe and unavoidable impurities, An austenitic stainless steel that satisfies the following formula (1). [Cr]+3.3[Mo]≧25.0 (1) Here, [Cr] and [Mo] are the Cr content (mass%) and Mo content (mass%) in the above-mentioned composition, respectively.
[0019] 2. The composition further comprises, in mass%, Al: 0.100% or less, Ti: 0.50% or less, Nb: 0.50% or less, Cu: 2.50% or less, W: 0.50% or less, V: 0.30% or less and B: 0.0100% or less 2. The austenitic stainless steel according to 1 above, containing one or more selected from the following: Effect of the Invention
[0020] According to the present invention, it is possible to obtain an austenitic stainless steel having excellent micro-corrosion resistance in the passive region while using a component composition that can be produced without using electroslag remelting (ESR). Furthermore, the austenitic stainless steel of the present invention has excellent micro-corrosion resistance in the passive region, and is therefore particularly advantageous when used in products such as in vivo implants, which require the prevention of elution of metal ions. [Brief description of the drawings]
[0021] [Figure 1] FIG. 2 is a diagram showing an example of an anodic polarization curve of an austenitic stainless steel. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] First, the composition of the austenitic stainless steel according to one embodiment of the present invention will be described. Note that the unit of the composition is always "mass %", but hereinafter, unless otherwise specified, it will be simply indicated as "%".
[0023] C: 0.100% or less C is an element that stabilizes the austenite phase. Therefore, the C content is preferably 0.003% or more. On the other hand, if the C content exceeds 0.100%, the workability decreases. Therefore, the C content is set to 0.100% or less. The C content is preferably 0.090% or less, and more preferably 0.080% or less.
[0024] Si:2.00% or less Si is an element that has a deoxidizing effect. To obtain such an effect, the Si content is preferably 0.01% or more. However, if the Si content exceeds 2.00%, the steel becomes hard and the workability decreases. Furthermore, since Si is an element that stabilizes the ferrite phase, it hinders the stabilization of the austenite phase. Therefore, the Si content is set to 2.00% or less. The Si content is preferably 0.50% or less, and more preferably 0.35% or less.
[0025] Mn: 2.00% or more and 7.00% or less Mn has the effect of increasing the amount of N dissolved in solid solution. In addition, Mn prevents cracks during hot rolling due to grain boundary segregation of S by combining with S present in the steel. In order to obtain such an effect, the Mn content is set to 2.00% or more. However, if the Mn content exceeds 7.00%, the amount of precipitated Mn sulfides increases, resulting in a decrease in pitting corrosion resistance. Therefore, the Mn content is set to 2.00 to 7.00%. The Mn content is preferably 2.50% or more. In addition, the Mn content is preferably 5.00% or less, more preferably 4.00% or less, and further preferably 3.50% or less.
[0026] P:0.070% or less P is an element that reduces toughness and corrosion resistance. Therefore, it is desirable to avoid mixing P into steel as much as possible. In particular, if the P content exceeds 0.070%, toughness and corrosion resistance are significantly reduced. Therefore, the P content is set to 0.070% or less. The P content is preferably 0.050% or less, and more preferably 0.040% or less. There is no particular lower limit for the P content, but excessive de-P leads to an increase in manufacturing costs. Therefore, the P content is preferably 0.010% or more.
[0027] S: 0.030% or less S is an element that causes cracks during hot rolling due to grain boundary segregation. S also reduces corrosion resistance. Therefore, it is desirable to avoid mixing S into steel as much as possible. In particular, if the S content exceeds 0.030%, hot rolling properties and corrosion resistance are significantly reduced. Therefore, the S content is set to 0.030% or less. The S content is preferably 0.010% or less, and more preferably 0.005% or less. There is no particular lower limit for the S content, but excessive de-S leads to an increase in manufacturing costs. Therefore, the S content is preferably 0.0001% or more.
[0028] Cr: 18.0% or more and 25.0% or less Cr is an element that strengthens the passive film formed on the surface of steel and improves corrosion resistance. To obtain such an effect, the Cr content is set to 18.0% or more. However, Cr is a ferrite stabilizing element. Therefore, if the Cr content exceeds 25.0%, it hinders the stabilization of the austenite phase and reduces workability. Therefore, the Cr content is set to 18.0% to 25.0%. The Cr content is preferably 19.0% or more, and more preferably 20.5% or more. Moreover, the Cr content is preferably 24.0% or less, and more preferably 23.0% or less.
[0029] Mo: 1.50% or more and 3.50% or less Like Cr, Mo is an element that strengthens the passive film formed on the surface of steel and improves corrosion resistance. To obtain this effect, the Mo content is set to 1.50% or more. However, if the Mo content exceeds 3.50%, it leads to a decrease in hot workability. Therefore, the Mo content is set to 1.50 to 3.50%. The Mo content is preferably 2.00% or more, and more preferably 2.30% or more. Moreover, the Mo content is preferably 3.00% or less, and more preferably 2.70% or less.
[0030] Ni: 5.0% or more and 12.0% or less Ni is an element that promotes the formation of the austenitic phase. In order to obtain an austenitic stainless steel, the Ni content must be 5.0% or more. However, if the Ni content exceeds 12.0%, it leads to a decrease in workability and makes it easier for cracks to occur. Therefore, the Ni content is set to 5.0 to 12.0%. The Ni content is preferably 8.0% or more, and more preferably 10.0% or more. In addition, the Ni content is preferably 11.0% or less.
[0031] Ag: 0.04% or more and 0.20% or less Ag is an important element that has the effect of suppressing the formation of micropits in the passive region. That is, Ag binds with chloride ions in the environment, weakening the aggressiveness of the chloride ions, promoting passivation by solid solution N, and suppressing the formation of micropits in the passive region. In order to obtain such an effect, the Ag content needs to be 0.04% or more. However, if the Ag content exceeds 0.20%, the material cost increases. In addition, the hot workability decreases, which causes edge cracks during hot rolling. Therefore, the Ag content is set to 0.04 to 0.20%. The Ag content is preferably 0.06% or more. The Ag content is preferably 0.10% or less.
[0032] N: 0.20% or more and 0.35% or less N is an important element that has the effect of promoting passivation and, when contained together with an appropriate amount of Ag, has the effect of suppressing the formation of micropits in the passive region. In order to obtain such an effect, the N content must be 0.20% or more. However, if the N content exceeds 0.35%, it cannot be manufactured by the usual vacuum induction melting method, and manufacturing by ESR is required, which increases the manufacturing cost. In addition, the formability is also reduced. Therefore, the N content is set to 0.20 to 0.35%. The N content is preferably 0.23% or more. The N content is preferably 0.30% or less, more preferably 0.25% or less.
[0033] [Cr]+3.3[Mo]≧25.0 (1) As described above, Cr and Mo are elements that strengthen the passive film formed on the surface of steel and improve corrosion resistance. Also, as described above, in order to maximize the passivation effect of solute N and obtain excellent micro-corrosion resistance, it is necessary to control the contents of Cr, Mo, Ag and N within the above ranges, and further, to make [Cr]+3.3[Mo] 25.0 or more. [Cr]+3.3[Mo] is preferably 26.0 or more, more preferably 27.0 or more. Here, [Cr] and [Mo] are the Cr content (mass%) and Mo content (mass%) in the above composition, respectively.
[0034] The basic components of the austenitic stainless steel according to one embodiment of the present invention have been described above. In addition to the above basic components, Al: 0.100% or less, Ti: 0.50% or less, Nb: 0.50% or less, Cu: 2.50% or less, W: 0.50% or less, V: 0.30% or less and B: 0.0100% or less, One or more selected from the above may be appropriately contained.
[0035] Al: 0.100% or less Al is an element having a deoxidizing effect. To obtain this effect, the Al content is preferably 0.010% or more. The Al content is more preferably 0.015% or more, and further preferably 0.020% or more. However, if the Al content exceeds 0.100%, there is a possibility that surface defects will occur due to aluminum nitride. Therefore, when Al is contained, its content is set to 0.100% or less. The Al content is preferably 0.080% or less, and more preferably 0.050% or less.
[0036] Ti: 0.50% or less Ti has the effect of preventing sensitization by bonding with C and N contained in the steel. In order to obtain such an effect, the Ti content is preferably 0.01% or more. The Ti content is more preferably 0.05% or more, and further preferably 0.10% or more. However, if the Ti content exceeds 0.50%, the material cost increases. In addition, there is a possibility that surface defects may occur due to Ti-based inclusions. Therefore, when Ti is contained, the Ti content is 0.50% or less, and preferably the Ti content is 0.20% or less.
[0037] Nb: 0.50% or less Like Ti, Nb has the effect of acting as a stabilizing element that prevents sensitization by bonding with C and N contained in the steel. To obtain such an effect, the Nb content is preferably 0.01% or more. The Nb content is more preferably 0.05% or more, and further preferably 0.10% or more. However, if the Nb content exceeds 0.50%, the material cost increases. In addition, there is a possibility that surface defects may occur due to Nb-based inclusions. Therefore, when Nb is contained, the Nb content is set to 0.50% or less. The Nb content is preferably 0.20% or less.
[0038] Cu:2.50% or less Cu is an element that stabilizes the austenite phase. Cu also has the effect of improving pitting corrosion resistance. In order to obtain such an effect, the Cu content is preferably 0.01% or more. The Cu content is more preferably 0.03% or more, and further preferably 0.05% or more. However, if the Cu content exceeds 2.50%, it leads to a decrease in hot workability. Therefore, when Cu is contained, the Cu content is 2.50% or less, and preferably 1.00% or less.
[0039] W: 0.50% or less W is an element that improves pitting corrosion resistance. In order to obtain such an effect, the W content is preferably 0.01% or more. The W content is more preferably 0.02% or more, and further preferably 0.03% or more. However, if the W content exceeds 0.50%, the material cost increases. In addition, it leads to a decrease in ductility. Therefore, when W is contained, the W content is 0.50% or less. The W content is preferably 0.20% or less, and more preferably 0.10% or less.
[0040] V: 0.30% or less V is an element that improves pitting corrosion resistance. To obtain such an effect, the V content is preferably 0.01% or more. The V content is more preferably 0.03% or more, and further preferably 0.05% or more. However, if the V content exceeds 0.30%, there is a possibility that surface defects will occur due to V-containing inclusions. Therefore, when V is contained, the V content is set to 0.30% or less. The V content is preferably 0.20% or less, and more preferably 0.10% or less.
[0041] B: 0.0100% or less B has the effect of preventing edge cracks during hot rolling. To obtain such an effect, the B content is preferably 0.0010% or more. However, if the B content exceeds 0.0100%, the corrosion resistance may decrease. Therefore, when B is contained, the B content is 0.0100% or less. The B content is preferably 0.0050% or less.
[0042] The other components are Fe and unavoidable impurities. Here, examples of unavoidable impurities include O. In order to prevent surface defects due to the formation of inclusions, the O content is preferably 0.05% or less.
[0043] Next, the structure of the austenitic stainless steel according to one embodiment of the present invention will be described. The structure of the austenitic stainless steel according to one embodiment of the present invention is essentially composed of an austenite phase (the volume fraction of the austenite phase is 99% or more). The structure of the austenitic stainless steel according to one embodiment of the present invention may contain inclusions and precipitates at a volume fraction of 1% or less as the remainder other than the austenite phase. Examples of the inclusions and precipitates include one or more selected from the group consisting of oxides, carbides, nitrides, sulfides, and intermetallic compounds.
[0044] The identification of each phase may be performed according to a conventional method. For example, when the austenitic stainless steel has the shape of a steel plate, a test piece is cut out from the steel plate with the rolling direction cross section (L cross section) as the observation surface. The test piece is then polished, and the structure of the center of the plate thickness (at t / 2 position, where t is the plate thickness of the steel plate) is observed by EBSD (electron backscatter diffraction method, magnification: 500 times). From the obtained photographed image, the type of structure (phase) is identified and the fraction (area ratio) of each structure (phase) is measured using image analysis software OIM Analysis manufactured by TSL Solutions.
[0045] The shape of the austenitic stainless steel according to one embodiment of the present invention is not particularly limited, and examples thereof include steel plate, steel bar, wire rod, and the like.
[0046] Next, a preferred method for producing an austenitic stainless steel according to one embodiment of the present invention will be described.
[0047] Molten steel having the above-mentioned composition is melted in a converter or an electric furnace, and then refined by vacuum oxygen decarburization (VOD) or argon oxygen decarburization (AOD), etc., and then subjected to continuous casting or billet rolling to be formed into any shape depending on the application, such as steel slabs, blooms, billets, etc. The billets may be further rolled into steel bars or wire rods.
[0048] For example, when manufacturing a steel sheet, a steel slab is heated to 1200 to 1300°C, and then hot-rolled to obtain a hot-rolled steel sheet. The obtained hot-rolled steel sheet is optionally subjected to hot-rolled sheet annealing and pickling. If necessary, shot blasting may be performed before pickling. Then, the hot-rolled steel sheet may be optionally cold-rolled to obtain a cold-rolled steel sheet. Then, the obtained cold-rolled steel sheet is optionally subjected to cold-rolled sheet annealing. Furthermore, the hot-rolled steel sheet or cold-rolled steel sheet may be subjected to finish rolling (final cold rolling) to obtain a desired sheet thickness. Also, finish annealing may be performed after finish rolling. The conditions of hot rolling, cold rolling, hot rolled sheet annealing, cold rolled sheet annealing, finish rolling and finish annealing are not particularly limited and may be in accordance with conventional methods. In addition, pickling may be performed after cold rolled sheet annealing. In addition, intermediate annealing may be performed during cold rolling. Furthermore, the cold rolled sheet annealing, intermediate annealing and finish annealing may be bright annealing. EXAMPLES
[0049] A 30 kg steel ingot having the composition shown in Table 1 (the balance being Fe and unavoidable impurities) was melted in a vacuum melting furnace, heated at 1200°C, and then hot-rolled to produce a sheet bar having a thickness of 30 mm. The sheet bar was cut to a length of 120 mm, and then the top and bottom of the sheet bar were ground by 2.5 mm to obtain a sheet bar having a thickness of 25 mm. Next, the sheet bar was heated again to 1200°C and hot-rolled to produce a hot-rolled steel sheet having a thickness of 4 mm. The hot-rolled steel sheet was cut to a length of 220 mm, and then hot-rolled at 1060°C. Next, the scale on the surface of the hot-rolled steel sheet was removed by shot blasting and grinding with a grinder. Next, the hot-rolled steel sheet was cold-rolled to produce a cold-rolled steel sheet having a thickness of 1.0 mm. This cold-rolled steel sheet was cut to a length of 200 mm, and then subjected to cold-rolled sheet annealing at 1060° C. Next, scale on the surface of the cold-rolled steel sheet was removed by shot blasting and grinding with a grinder.
[0050] The micro-corrosion resistance of the steel sheets thus obtained was evaluated in the following manner. When the structure of the obtained steel sheets was observed in the same manner as above, the volume fraction of the austenite phase was 99% or more in the structure of each steel sheet.
[0051] -Evaluation of micro-corrosion resistance Predetermined test pieces were taken from the steel plates obtained as described above, and the microcorrosion resistance was evaluated in an environment simulating the inside of a living body. Specifically, a 0.9 mass% NaCl aqueous solution at 37°C was used as the test solution without degassing, and the test piece was immersed in the test solution. Next, in accordance with the method for measuring pitting corrosion potential specified in JIS G 0577, the natural immersion potential was measured at a current density of 1.1 mA cm -2 Potential sweep rate 20 mV min -1 The potential was swept with a 10000V AC / 10000 Hz. The reference electrode was Ag / AgCl (saturated KCl). In addition, before measuring the pitting potential, the test pieces were passivated by immersing them in a 30% by mass aqueous nitric acid solution at 50°C for 1 hour, and then dry-polished with #600 abrasive paper.
[0052] For all steel types, the current density was 100 μA cm -2 Potential reached: V C’100 The current density was 1 μA cm−1 in the potential range of 200 to 400 mV vs. Ag / AgCl for all steels, and the current density was 1 μA cm−1 in the potential range of 200 to 400 mV vs. Ag / AgCl for all steels. -2 The potential sweep was stopped at 200 mV vs. Ag / AgCl and 400 mV vs. Ag / AgCl, and the surfaces of the test pieces were observed. No pitting corrosion visible to the naked eye was observed for any of the steel test pieces. From this, it is believed that the potential range of 200 to 400 mV vs. Ag / AgCl corresponds to the passive region for all steel types.
[0053] From the above viewpoints, the potential range of 200 to 400 mV vs. Ag / AgCl was set as the representative potential range in the passive region. Then, the current frequency was measured in the representative potential range as described above, and the microcorrosion resistance was evaluated according to the current frequency according to the following criteria. The results are shown in Table 1. 〇 (Pass): Current frequency is less than 250 × (Fail): Current frequency is 250 or more
[0054] It can be said that the higher the current frequency, the more micropits are formed and repaired. In fact, when the surface of test pieces with a current frequency of 250 or more was examined with an optical microscope, numerous micropits were confirmed. Therefore, if the same austenitic stainless steel as these test pieces is used in a fluid simulating the body, metal ions will be eluted. On the other hand, in test pieces with a current frequency of less than 250, the elution of metal ions was significantly suppressed compared to conventional methods.
[0055] [Table 1]
[0056] As can be seen from Table 1, all of the inventive examples had excellent microcorrosion resistance.
[0057] On the other hand, in the comparative samples Nos. 22 and 23, the Ag content was less than 0.04%, so that the passivation effect of the dissolved N was not sufficiently obtained, and the microcorrosion resistance was poor. In sample No. 24, the N content was less than 0.20%, so the passivation effect of the dissolved N was not sufficient, and the microcorrosion resistance was poor. In sample No. 25, since [Cr]+3.3[Mo] was less than 25.0, the passivation effect of the dissolved N was not maximized, and sufficient microcorrosion resistance was not obtained.
Claims
1. In mass percent, C: 0.100% or less, Si: 2.00% or less, Mn: 2.00% or more and 7.00% or less, P: 0.070% or less, S: 0.030% or less, Cr: 18.0% or more and 25.0% or less, Mo: 1.50% or more and 3.50% or less, Ni: 5.0% or more and 12.0% or less, Ag: 0.04% or more and 0.20% or less; N: 0.20% or more and 0.35% or less and the balance being Fe and unavoidable impurities, An austenitic stainless steel that satisfies the relationship of the following formula (1). [Cr]+3.3[Mo]≧25.0...(1) Here, [Cr] and [Mo] are the Cr content (mass%) and Mo content (mass%) in the above-mentioned composition, respectively.
2. The composition further comprises, in mass%, Al: 0.100% or less, Ti: 0.50% or less, Nb: 0.50% or less, Cu: 2.50% or less, W: 0.50% or less, V: 0.30% or less; B: 0.0100% or less The austenitic stainless steel according to claim 1, further comprising one or more selected from the following:
Citation Information
Patent Citations
Non-magnetic stainless steel for medical apparatuses and instruments and manufacturing method of non-magnetic stainless steel
CN106048410A
Austenitic stainless steel excellent in sulfuric acid corrosion resistance
JP1999189848A
Stainless steel excellent in antibacterial property and its production
JP2001011584A
Two-phase stainless steel
JP2020186441A
Austenitic stainless steel
JP2020196912A